Comparison of Retrograde Intrarenal Surgery with Ureteral Access Sheath in Stented versus Non-Stented Patients - Hussain, Atif; ur Rehman, Assad; Ijaz, Muhammad Ahmad; Ali, Sharafat; Nusrat, Nadeem (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the outcomes of retrograde intrarenal surgery in patients with and without preoperative ureteral stenting, and to identify predictors of stone-free rate. Method: The prospective, observational study was conducted from March to June 2025 at the Pakistan Kidney and Liver Institute and Research Centre, Lahore, Pakistan, and comprised patients aged 16-75 years having renal calculi 1-2cm who underwent retrograde intrarenal surgery with ureteral access sheath. The stented patients were in group A, while the non-stented patients were in group B. Perioperative, clinical and demographic data was noted. At 4-6 weeks postoperatively, non-contrast computed tomography scan of the kidney-ureter-bladder region was done to assess the non-presence of stones. Data was analysed using SPSS 27. Results: Of the 217 patients, 102(47%) were in group A; 65(66.7%) males and 37(33.3%) females with mean age 41.16±12.96 years. There were 115(53%) patients in group B; 74(69.6%) males and 41(30.4%) females with mean age 43.30±13.66 years (p>0.05). Access sheath insertion was more successful in group A (p<0.001) and the length of hospital stay was shorter (p=0.002) compared to group B. Stone-free rates were better in group A, but the difference with group B was not statistically significant (p=0.053). Two factors were strong predictors of stone-free rate: smaller stone size (p<0.001) and absence of hypertension (p=0.049). Conclusion: Preoperative stenting, which improved access sheath success and reduced the length of hospital stay, may offer perioperative advantages towards selected cases. Smaller stone size and absence of hypertension independently predicted better stone-free rate following retrograde intrarenal surgery. Key Words: Ureteroscopy, Ureteral stents, Ureteral access sheaths, Kidney calculi, Treatment outcome.